Lymphocyte proliferation in common variable immunodeficiency (CVID) patients by carboxyfluorescein succinimidyl ester (CFSE) - AKKOÇ, TUNÇ; ÖĞÜLÜR, İSMAİL; AYDINER, ELİF; BARIŞ, SAFA (My University, 2011)
Objective: Common variable immunodeficiency (CVID) is a heterogeneous disease in the group of predominantly antibody deficiencies, which is defined by hypogammaglobulinemia and normal or low level of B cells, and characterized by increased susceptibility to recurrent bacterial infections, autoimmune disorders, and malignancies. In this study, we aimed to investigate the proliferation of the B and T lymphocytes in patients with CVID.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Ekoloji ve Hidroklimatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Medical Ecology and Hydroclimatology; Health Sciences; TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); Araştırma ve Teori; İncelemeler ve Referanslar (tıbbi); Research and Theory; Reviews and References (medical); CVID; CFSE; Lymphocytes proliferation; T lymphocyte isolation; B lymphocyte isolation